Delay- and Disruption-Tolerant Networking - FARRELL, STEPHEN (IEEE, 2009)
Delay- and disruption-tolerant networking (DTN) grew out of attempts to develop an interplanetary Internet but has evolved into an active area of networking research, with applications in space networking, military tactical networking, and networking for various challenged communities. The DTN Research Group provides an open forum in which DTN researchers and developers can collaborate to further develop this experimental technology.
PUBLISHED
Keywords: DTN; Internet protocol